Improving Knowledge of Line Follower Robots at SMP Muhammadiyah 1 Godean - Anna Nur Nazilah Chamim; Muhamad Yusvin Mustar; Kunnu Purwanto; Rama Okta Wiyagi; Gardiya Septriadi; Khusni Abbasf (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2022)
Robotics is one of the fields of study that is closely related to several other subjects such as mathematics, science, and technology. Studying robotics will obviously be very beneficial for students. There is no exception for students of SMP Muhammadiyah 1 Godean who do not yet have a curriculum or extra-curricular about robotics. One of the efforts to increase knowledge about robotics, especially line follower robots, is a training on how to assemble and test the robot. In collaboration with the service team from the University of Muhammadiyah Yogyakarta, the training activities were carried out with 30 students from grade 7. In this training, 10 line follower kid robots were used and a track field for the arena to test the success of the assembly. In this activity, a pre-test was carried out with an average result of 43% of participants who answered correctly. At the end of the training, a post-test was conducted with the average result of participants who answered correctly as much as 90%. It can be concluded that there is an increase in knowledge about robotics by the participants by 47%.